ISOLATION OF ESTERASE PRODUCING LACTOBACILLUS BREVIS NJ13 FROM KIM- CHI AND INVESTIGATION OF EFFECTIVE MEDIUM INGREDIENTS FOR ESTERASE PRODUCTION USING STATISTICAL METHOD - C. H. Kim; S. B. Cho; J.I. Chae; D. W. Kim; A R. Lee; J. K. Park; N. J. Choi (Journal of Animal and Plant Sciences, 2013)
In this study, an esterase producing Lactobacillus brevis NJ13 was firstly isolated from Kim-chi, a Korean traditional fermented cabbage. The isolation was based on esterase screening method using tributyrin and 16S ribosomal RNA gene sequence analysis. Its esterase was characterized and the effects of medium ingredients on esterase production were investigated. L. brevis NJ13 esterase was highly specific toward p-nitrophenyl butyrate (C4 acyl group) and showed maximum activity at a temperature of 50°C and pH 8.0. The esterase was resistant to various organic solvents, especially N,N-dimethylformamide. Triton X 100, MnCl2 and EDTA strongly inhibited the esterase, but CaCl2 induced the activation of the esterase. Six medium ingredients were examined for their effects on esterase production using the Plackett-Burman design. Olive oil and glucose negatively affected the production of esterase, while soybean oil, tributyrin, sucrose and CaCl2 displayed a positive effect. The effects were significant only for tributyrin and CaCl2. Therefore, the present study is providing the primary information for the esterase from L. brevis NJ13 and its optimumesterase producing fermentation conditions.
Keywords: Characterization; Esterase; Lactobacillus brevis; Medium ingredients; Plackett-Burman design